Uplift, climate and biotic changes at the Eocene–Oligocene transition in south-eastern Tibet. Issue 3 (12th June 2018) - Su, Tao; Spicer, Robert A; Li, Shi-Hu; Xu, He; Huang, Jian; Sherlock, Sarah; Huang, Yong-Jiang; Li, Shu-Feng; Wang, Li; Jia, Lin-Bo; Deng, Wei-Yu-Dong; Liu, Jia; et al.
Abstract: The uplift history of south-eastern Tibet is crucial to understanding processes driving the tectonic evolution of the Tibetan Plateau and surrounding areas. Underpinning existing palaeoaltimetric studies has been regional mapping based in large part on biostratigraphy that assumes a Neogene modernization of the highly diverse, but threatened, Asian biota. Here, with new radiometric dating and newly collected plant-fossil archives, we quantify the surface height of part of the south-eastern margin of Tibet in the latest Eocene (∼34 Ma) to be ∼3 km and rising, possibly attaining its present elevation (3.9 km) in the early Oligocene. We also find that the Eocene–Oligocene transition in south-eastern Tibet witnessed leaf-size diminution and a floral composition change from sub-tropical/warm temperate to cool temperate, likely reflective of both uplift and secular climate change, and that, by the latest Eocene, floral modernization on Tibet had already taken place, implying modernization was deeply rooted in the Palaeogene.